2013
DOI: 10.1155/2013/949107
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Purification of Postfermentation Medium after 1,3-PD Production from Raw Glycerol

Abstract: 1,3-Propanediol (1,3-PD) is an important chemical product which can be used to produce polyesters, polyether, and polyurethanes. In the process of conversion of glycerol to 1,3-PD by Clostridium large number of byproducts (butyric, acetic and lactic acid) are generated in the fermentation medium. The aim of this work was to isolate bacteria strains capable of the utilization of these byproducts. Screening of 30 bacterial strains was performed using organic acids as carbon source. Selected isolates were taxonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The method of artificially constructing microbial co-culture system can reduce the concentration of by-products and improve the synthetic efficiency of products. For instance, Daria et al co-cultured Alcaligenes faecalis JP1 and Clostridium butyricum DSP1 for 1,3-PDO synthesis [ 41 ]. In this system, the 1,3-PDO yield and productivity were increased to 0.53 g/g and 1.07 g/(L h), respectively, and the only by-product butyrate was less than 1 g/L [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of artificially constructing microbial co-culture system can reduce the concentration of by-products and improve the synthetic efficiency of products. For instance, Daria et al co-cultured Alcaligenes faecalis JP1 and Clostridium butyricum DSP1 for 1,3-PDO synthesis [ 41 ]. In this system, the 1,3-PDO yield and productivity were increased to 0.53 g/g and 1.07 g/(L h), respectively, and the only by-product butyrate was less than 1 g/L [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Daria et al co-cultured Alcaligenes faecalis JP1 and Clostridium butyricum DSP1 for 1,3-PDO synthesis [ 41 ]. In this system, the 1,3-PDO yield and productivity were increased to 0.53 g/g and 1.07 g/(L h), respectively, and the only by-product butyrate was less than 1 g/L [ 41 ]. However, the selection of appropriate host allocation metabolic pathway still faces many engineering problems, such as the complex subspecies dynamics/interaction, short stable production time, and unsatisfactory culture of microbial community and so on [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The titer, yield and productivity of 1,3‐PDO were 40 g L −1 (specific data not shown), 0.53 g g −1 and 1.07 g (L·h) −1 , respectively. More importantly, the sole by‐product of butyrate was less than 1 g L −1 128 …”
Section: 3‐pdo Production By Using Microbial Co‐culturementioning
confidence: 98%
“…A final product concentration as high as 70 g/l was obtained in fed-batch cultivation with a productivity of 2.6 g/l h. This study showed that 1,3-PD production in mixed culture achieved the same levels of product titer, yield, and productivity as in typical pure cultures, especially without sterile requirement. Szymanowska-Powalowska et al ( 2013 ) isolated bacterial strains with capability of the utilization of by-products such as butyric acid and lactic acid. The co-culture of Clostridium butyricum DSP1 producing 1,3-PD and Alcaligenes faecalis JP1 utilizing organic acids increased the volumetric productivity (1.07 g/l h) and yield of 1,3-PD (0.53 g/g).…”
Section: Comparison Between Pure Culture Of Single Strain and Mixed Cmentioning
confidence: 99%